The Zimbabwe liberation war family in selected war novels - implications to post-independence governance - Charamba, Tyanai; Dlodlo, Sindile (Africa Institute for Culture, Peace, Dialogue & Tolerance Studies, 2022)
The Zimbabwean war novel treats the political family that emerged during the Zimbabwean liberation struggle. That struggle is popularly known as the Second Chimurenga. The Chimurenga was fought in earnest from 1973 to 1979. During that struggle for independence, the nationalist ideology was embedded in the traditional Zimbabwean family kinship ties. That is the case since nationalist leaders and combatants harnessed structures of the traditional Shona family to mobilize the general populace to partake in the struggle against Prime Minister Smith’s unilateralist rule. Using selected war novels, this effort exposes and critiques the nature of family ties,kinship titles, roles and responsibilities that the liberation war participants emphasised when they struggled to mould a national ethos for Zimbabwe. Further, the effort critically examines the implications of resorting to traditional family structures when a people seek to come up with a political family and seek to assert and reassure nationhood and good governance. Three novels have been selected for use in this research. They are: Harvest of thorns (Chinodya, 1989), Vavariro (Choto, 1989) and Echoing silencies (Kanengoni 1997). Three family relationships have been Selected for the the discussion. These are parent/child, brother/sister and brother/brother’. They are selected since they are prevalent in the selected novels.